Morpho-genetic characterization of fig (Ficus carica var. rupestris (Hausskn.) Browicz) genotypes to be used as rootstock - Yildiz, Ercan; Ağlar, Erdal; Sümbül, Ahmet; Yaman, Mehmet; Caliskan, Oğuzhan; Popescu, Gheorghe Cristian; Popescu, Monica; Gönültaş, Metin (Genetic resources and crop evolution, 2024)
With its enormous genetic pool, Türkiye is the homeland of the fig and many plant species. The common fig species in the country's natural population are Ficus carica var. caprificus (male figs), Ficus carica var. domestica (female figs; edible figs), and Ficus carica var. rupestris . In this study, the morphological and molecular characterization of 42 genotypes, including those obtained by selection from the Ficus carica var. rupestris (Hausskn.) Browicz population, which is naturally spread in a limited area in Tunceli province, was performed. This study evaluated the qualitative and quantitative characteristics of 23 fig genotypes. These results showed that tree growth habit, lateral shoot formation, apical dominancy, and leaf length characteristics were highly discriminant variables for phenotypic description in wild fig genotypes. The genetic relationship between the genotypes was demonstrated with 12 SRAP and 9 ISSR primers. As a result of the study, it was determined that the genetic similarity values ranged between 0.52 and 0.94. It was determined that the first five essential components (PCA) contributed 20.87%, 13.21%, 10.66%, 9.58%, and 7.11% of the total variation, respectively, and their cumulative rate corresponded to 61.43% of the total variation. Very detailed results on the genetic variation in the fig population in the region were obtained by morphological features and molecular methods. The seven genotypes selected were propagated to determine their potential for dwarf rootstocks. The results of the present study may provide significant leads for further research on this subject. The potential of dwarf rootstocks in figs can be an essential tool for modern fruit growing.